1988
DOI: 10.1093/cvr/22.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of the ventricular paced QT interval in response to abrupt changes in pacing rate

Abstract: The rate of QT adaptation to abrupt changes in pacing rate was studied in seven patients with newly diagnosed complete heart block with a ventricular escape rate of less than 40 beats.min-1. Their median age was 70 (range 36-84) years, and none was taking any cardioactive medication known to affect the QT interval. From a baseline pacing rate of 50 or 110 beats.min-1 the ventricular rate was increased or decreased to a new level. The time taken for the ventricular paced QT interval to complete 90% of the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 0 publications
12
121
1
2
Order By: Relevance
“…According to the results in Pueyo et al (2004), the QT interval requires nearly 2.5 min to follow HR changes, in mean over patients, although both the duration and profile of QT hysteresis are found to be highly individual. In agreement with Lau et al (1988), the adaptation process is shown to be composed of two distinct phases: fast and slow. The methodology described in Pueyo et al (2004) has been extended later on in Pueyo et al (2008) to include beat-to-beat variations of QT dependency on HR, i.e.…”
Section: (A ) Qt Adaptation To Hr Changessupporting
confidence: 73%
“…According to the results in Pueyo et al (2004), the QT interval requires nearly 2.5 min to follow HR changes, in mean over patients, although both the duration and profile of QT hysteresis are found to be highly individual. In agreement with Lau et al (1988), the adaptation process is shown to be composed of two distinct phases: fast and slow. The methodology described in Pueyo et al (2004) has been extended later on in Pueyo et al (2008) to include beat-to-beat variations of QT dependency on HR, i.e.…”
Section: (A ) Qt Adaptation To Hr Changessupporting
confidence: 73%
“…In the literature, QT hysteresis has been evaluated under various conditions. In [60] the ventricular paced QT interval was shown to take between 2 and 3 minutes to follow a change in HR, with the adaptation process presenting two phases: a fast initial phase lasting for a few tens of seconds and a second slow phase lasting for several minutes. In [59], QT adaptation was analyzed after a provoked HR change or after physical exercise and the QT hysteresis lag was of some minutes.…”
Section: ) Qt Adaptation To Hr Changesmentioning
confidence: 99%
“…The initial adaptation (around 50%) of QT change occurs the order of a 50 to 60 s time frame, the terminal adaptation lasting above 2 min. 4,15,18 Less is known about QT hysteresis during physiologic HR fluctuation not associated with atrial pacing or acute exercise. In a recent study, Pueyo et al showed that the hysteresis phenomenon was different among subjects and was also influenced by amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…Following an abrupt change in HR, the QT adaptation is not immediate but is achieved within a 3-min time frame, although most QT adaptations occur over the first minute. 4,14,15 From a theoretical point of view, QT interval measurement performed just after a sudden HR change would lead to a potential error in the estimation of QT duration. Thus, the rate correction of QT interval duration based on the single preceding RR interval may introduce a potential confounding factor whatever the strategy used to correct QT interval.…”
Section: Introductionmentioning
confidence: 99%